Cardiometabolic Risk Factors Among Insufficiently Active African American Women With Obesity: Baseline Findings From Smart Walk. Issue 2 (5th March 2023) - Joseph, Rodney P.; Ainsworth, Barbara E.; Vega-López, Sonia; Adams, Marc A.; Todd, Michael; Gaesser, Glenn A.; Keller, Colleen
Abstract : Background: Low moderate-to-vigorous physical activity (MVPA) levels and obesity are associated with increased cardiometabolic disease risk. Objective: The aim of this study was to describe MVPA and cardiometabolic risk characteristics of insufficiently active African American women with obesity (N = 60) enrolled in a culturally tailored MVPA intervention. Methods: We assessed accelerometer-measured and self-reported MVPA, blood pressure, serum lipid profiles, cardiorespiratory fitness (VO2 peak), and aortic pulse wave velocity. Results: Participants (mean age, 38.4; mean body mass index, 40.6 kg/m 2 ) averaged 15 min/d of accelerometer-measured MVPA and 30 min/wk of self-reported MVPA. Systolic and diastolic blood pressure levels were elevated (135.4 and 84.0 mm Hg, respectively). With the exception of low-density lipoprotein cholesterol (121.4 mg/dL) and high-density lipoprotein cholesterol (47.6 mg/dL), lipid profiles were within reference ranges. Compared with normative reference values, average VO2 peak was low (18.7 mL/kg/min), and pulse wave velocity was high (7.4 m/s). Conclusions: Our sample of insufficiently active African American women with obesity was at an elevated risk for cardiometabolic disease.